2015
DOI: 10.2147/jn.s74138
|View full text |Cite
|
Sign up to set email alerts
|

Developmental history of neurorestoratology

Abstract: Abstract:The aim of neurorestoratology is to restore, promote and maintain the integrity of impaired or lost neuronal functions and/or structures, using novel cell-based comprehensive neurorestorative strategies. The purpose of this review is to briefly introduce the developing history of neurorestoratology, which includes neurorestorative strategies, the basis of central nervous system neurorestorable theory, communities in the field of neurorestoratology, and journals related to neurorestoratology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 110 publications
0
6
0
Order By: Relevance
“…The American Spinal Injury Association (ASIA) neurological score is the most widely used quantitative neurological assessment. Quality of life is evaluated using the International Association of Neurorestoratology SCI Functional Rating Scale [14,15].…”
Section: Acute and Subacute Stages Of Sci 21 Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The American Spinal Injury Association (ASIA) neurological score is the most widely used quantitative neurological assessment. Quality of life is evaluated using the International Association of Neurorestoratology SCI Functional Rating Scale [14,15].…”
Section: Acute and Subacute Stages Of Sci 21 Assessmentmentioning
confidence: 99%
“…In addition to treatment of the primary injury, secondary SCI requires attention [9,[14][15][16]. The main purpose of SCI treatment is to reduce secondary injury in the acute and subacute stages.…”
Section: Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings obtained about clinical trials for SCI treatment demonstrated that the efficacy of MSCs in human studies is not beneficial like in preclinical studies [45]. For these reasons protocol standardization of basic and preclinical studies using MSCs should emphasize to translate to the clinical setting.…”
Section: Introductionmentioning
confidence: 99%